Crosby Noyes Boyd autograph collection - Boyd, Crosby Noyes, 1903-; Noyes, Crosby Stuart, 1825-1908.
Correspondence, appointments, genealogical material, receipts, sketches, and signatures originally collected by Boyd's grandfather, Crosby Stuart Noyes (1825-1908), editor-in-chief of The Washington Evening Star, and relating, in part, to him or the newspaper. Includes letters of James Gillespie Blaine, Belle Boyd, Lewis Cass, Mark Twain (Samuel L. Clemens), Jefferson Davis, Frederick Douglass, Thomas Jefferson, Amos Kendall, Abraham Lincoln, Herman Melville, Emma Dorothy Eliza Nevitte Southworth, William Howard Taft, and Victoria C. Woodhull.
Autograph collector.
Keywords: Statesmen -- Autographs; Washington star (Newspaper); Genealogy; American newspapers -- Washington (D.C.); Noyes, Crosby Stuart, -- 1825-1908.; Blaine, James Gillespie, -- 1830-1893 -- Correspondence; Boyd, Belle, -- 1844-1900 -- Correspondence; Cass, Lewis, -- 1782-1866 -- Correspondence; Twain, Mark, -- 1835-1910 -- Correspondence; Davis, Jefferson, -- 1808-1889 -- Correspondence; Douglass, Frederick, -- 1818-1895 -- Correspondence; Jefferson, Thomas, -- 1743-1826 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; Lincoln, Abraham, -- 1809-1865 -- Correspondence; Melville, Herman, -- 1819-1891 -- Correspondence; Southworth, Emma Dorothy Eliza Nevitte, -- 1819-1899 -- Correspondence; Taft, William H. -- 1857-1930 -- Correspondence; Woodhull, Victoria C. -- 1838-1927 -- Correspondence; The Washington Evening Star; Newspaper editors